Missionarische Bewegung und soziale Differenzierung im Katholizismus: Die Praxis der Gebietsmission in der Bundesrepublik 1950-1960 - Ziemann, Benjamin (Kirchliche Zeitgeschichte, 2004)
The social changes which took place in West Germany in the immediate post-1945 years were immense. This caused grave problems for the Catholic Church, especially for its attempted missionary endeavours. These were based on a French model and sought to refashion the traditional forms of popular public missions. The plan was to draw up a kind of sociography of the region to be missionized, breaking it down into various categories, and adapting the missionary work accordingly so that the members of religious orders who were engaged for this work could see more clearly what was required. But by the time of the preparatory missions for the 1960 World Eucharistie Congress held in Munich, it was clear that the age of ecclesiastical triumphalism had past. The new social realities in West Germany showed that new answers were required along with a thorough reorganization of the Catholic Church's structures.